Assessment of Apical Periodontitis in Dogs and Humans: A Review. (March 2014) - Menzies, Robert A.; Reiter, Alexander M.; Lewis, John R.
Veterinary dentists commonly encounter apical periodontitis in dogs. An overview of the disease is presented, concentrating on pathogenesis and mechanisms of healing. Assessment modalities are reviewed and interpretations of treatment success and failure are discussed. The limitations of readily available diagnostic equipment are illustrated. The benefits of identifying the causative agent and resultant pathosis should not be overlooked. Well-designed clinical studies evaluating various methods of long-term follow-up for apical periodontitis in dogs are needed.